Ultra-fast Suzuki and Heck reactions for the synthesis of styrenes and stilbenes using arenediazonium salts as super-electrophiles; Organic Chemistry Frontiers; Vol. 5, iss. 1 - Trusova M. E. Marina Evgenievna; Rodriguez-Zubiri M. Mireia; Kutonova K. V. Ksenia; Jung N. Nicole; Brase S. Stefan; Francois-Xavier F. Felpin; Postnikov P. S. Pavel Sergeevich (2018, 2018)
Title screen